1980
DOI: 10.1093/bja/52.suppl_1.3s
|View full text |Cite
|
Sign up to set email alerts
|

The Emergence of ORG NC 45, 1- [(2β,3α, 5α,16β, 17β)-3, 17-BIS(Acetyloxy)-2-(1-Piperidinyl)-Androstan-16-YL]-1-Methylpiperidinium Bromide, from the Pancuronium Series

Abstract: A novel approach is described for obtaining a drug that will be a potent non-depolarizing neuromuscular blocking agent with the potential for a short duration of action and little cumulative effect. This approach led to the discovery of Org NC 45, from the pancuronium series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
3

Year Published

1983
1983
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(22 citation statements)
references
References 0 publications
1
18
0
3
Order By: Relevance
“…Vecuronium undergoes spontaneous deacetylation to three alcohol metabolites (35). The main metabolite, 3a,37P-diol, is only 2% as potent as the parent drug (Fig.…”
Section: Metabolism and Excretionmentioning
confidence: 99%
“…Vecuronium undergoes spontaneous deacetylation to three alcohol metabolites (35). The main metabolite, 3a,37P-diol, is only 2% as potent as the parent drug (Fig.…”
Section: Metabolism and Excretionmentioning
confidence: 99%
“…Vecuronium (Org NC 45), a recently introduced competitively acting muscle relaxant (Savage et al, 1980;Agoston et al, 1980), is chemically related to pancuronium and it was therefore of interest to test whether any potentiation occurs when these two related drugs are administered in combination. This has been investigated clinically in the present study.…”
Section: Introductionmentioning
confidence: 99%
“…This feature favors hepatic uptake of VB. It is also speculated that VB is transported into the hepatic cell by a carrier-mediated process 2 1 • In earlier studies, VB in aqueous solution was found to be hydrolyzed spontaneously within 30 min 25 and VB in plasma was hydrolyzed at a rate of 0.3%10 at neutral pH and room temperature. We examined the decomposition of VB and Org NC 58 (ISTD) in methanol at a concentration of 100 J.Lg·ml-1 • Both VB and Org NC 58 were stable for several months at the concentration when stored at 4°C, but 30% of VB and 80% of Org NC 58 were decomposed at room temperature in ten hours.…”
Section: Discussionmentioning
confidence: 99%